Pengaruh Dimensi Struktural, Dimensi Rasional, dan Dimensi Kognitif Modal Sosial terhadap Persepsi Kinerja Perangkat Desa di Kabupaten Kudus - Luthfi, Muhammad; Susanti, Martien Herna; Sumarno, Sumarno (Universitas Negeri Semarang, 2017)
Village should be able to provide optimal service, either through the village official performance or the rules which support the village development process. As one of the element in village government, village officials are appointed, to help run errands village chief administrativelyas well as implement policy, and dismissed by village head. Therefore, besides on the chief, the central of a village is on the village officials. The population in this study were 1955 people of village officials, while the sample taken were 95 people of village officials. The method used in this study involved questionnaire, documentation, observation and interview. The data analysis used descriptive-analysis of percentage, multiple linear regression testing analysis and hypothesis testing analysis. The result of multiple regression equation obtained from the is Y=1.380+0.314 Xâ‚+0.533Xâ‚‚+0.803Xâ‚ƒ. From the regression equation test with F-test equation, obtained that F = 61.570 with 0,000 < 0,05 significance. This result shows that F is significant, so the influence of structural, rational and cognitive dimension of social modal affect the performance of the village officials as much as 65,8%, while the influence for each dimension partially are 7,18% for structural dimension, 11,90% for rational dimension, and 17,47% for cognitive dimension. It can conclude in this study that there are positive influence and significant structural, rational and cognitive dimension to the village officials in Kudus district.